¿Écfrasis o hipotiposis?: enargeia y retórica visual en la poesía del Siglo de Oro - Adolfo R. Posada (E-Spania, 2020)
The diverse descriptive modalities subscribed to the so-called literary pictorialism within the doctrine of ut pictura poesis in the Spanish Golden Age are not only limited to the phenomena and strategies nowadays related to the ekphrasis. A number of manifestations in the Spanish Renaissance and Baroque poetry, connected to the enargeia and the visual rhetoric, do not necessarily respond to verbal transpositions and the meta-representative quality of the description of art. The theory of the description in the Spanish Golden Age was indeed much more flexible and dynamic, so that there was no clear distinction in Cervantes’ time between ekphrasis –verbal representations of objects of art–, and hypotypose, understood as the vivid and evident description of reality as a work of art. This problem is essential for reconstructing the poetic vision shared by the Spanish Golden Age writers over the ciceronian verbis depingere from the Classical Age and the Renaissance and Baroque verbal paintings. Taking into account this issue, this article focuses on the defence of a complementary theoretical model to the ekphrasis paradigm, based on the pictorialist technique linked to the verbis depingere and the rhetorical figure of hypotypose as an analytical instrument, since it helps to study the nature of the literary image in the Spanish Golden Age beyond the transpositions of art.